A Mirza's Demands for Women, Cot and Cattle: A Multilingual Performance in Medieval Odisha. (April 2016) - Bedamatta, Urmishree
This article examines a multilingual folk theatrical performance called Mughal Tamsa. This polyglot theatrical form is considered the predecessor of the modern jatra (a stage performance with light and sound accompaniments) in Odisha and it was a popular form of entertainment in the medieval period. The central character of this performance is a Mughal mirza (prince) who is notorious among his subjects for his misrule and also for his unlawful demands for chhokri (women), bakri (cattle) and chhappar khat aur masuri (cot and other luxury goods). However, his servants thwart his ambitions with a playful and subversive interlinguality. How the various socio-cultural and historical trends may have given rise to the form and content of the Tamsa has been discussed in this article. This article argues that the Tamsa was a natural embodiment of the encounter of languages and cultures.